Importancia del médico en la sociedad; su papel en el seguro social - Jaramillo Antillón, Juan (2010)
For centuries, man was considered a herd of individuals by kings, pharaohs and priests in various placeson Earth. Its usefulness was due to the use made of it, to work as domestic servants , slaves, agriculture and the military.